Mesari (Melajah Aksara Bali): Interactive Multimedia Based on Local Wisdom for Seventh Grade in Junior High School - Bramasta, I Gede Bayu; Suartama, I Kadek; Sudarma, I Komang (Universitas Pendidikan Ganesha, 2022)
This development research is backgrounded by the absence of interactive multimedia in Balinese script learning. So it is deemed necessary to develop interactive multimedia in Balinese script learning. This study aims to describe the process of developing and validity of interactive multimedia Mesari (Melajah Aksara Bali) based on local wisdom for seventh grade. This development research uses the ADDIE model. The subjects of this study were content experts, design experts, media experts, three students in an individual trial, and nine students in a small group trial. The data collection method used is a questionnaire. Data analysis techniques use qualitative and quantitative descriptive analysis techniques. The results of the learning content expert test were obtained by 93,33%, the learning design expert test by 80,00%, the learning media expert test by 94.66%, the individual trial by 95,33%, and the small group trial by 92,22%, whose overall score percentage was qualified very well. The implication of this study is to provide Balinese script learning media to students and motivate teachers to create learning media that increase student learning motivation in the classroom.